2017
DOI: 10.20396/cel.v59i3.8651000
|View full text |Cite
|
Sign up to set email alerts
|

Basic research in phonology, resources and applications–the case of frequency

Abstract: É crescente a valorização da conversão do conhecimento fundamental desenvolvido pelos cientistas em produtos concretos, socialmente relevantes. No Laboratório de Fonética da Universidade de Lisboa tem-se trabalhado nos últimos anos tanto em domínios de investigação fundamental, como de investigação aplicada. Neste artigo é feita uma revisão dos principais recursos recentemente disponibilizados à comunidade por este Laboratório visando o acesso a informação sobre frequência fonológica e lexical. São sumariament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…1Indeed, vowel quality is highly correlated with stress position in EP: stressed syllables always exhibit unreduced vowels, whereas unstressed syllables may show reduced vowels (the most common pattern due to phonological vowel reduction) or unreduced ones. A computation of the distribution of reduced and unreduced vowels in unstressed positions, using the 5,294 most frequent word types from the FrePOP Lexicon (Vigário et al, 2015) which represent a corpus of over 2.6 million tokens, shows that 91.5% of all vowels in unstressed position are reduced vowels.…”
mentioning
confidence: 99%
“…1Indeed, vowel quality is highly correlated with stress position in EP: stressed syllables always exhibit unreduced vowels, whereas unstressed syllables may show reduced vowels (the most common pattern due to phonological vowel reduction) or unreduced ones. A computation of the distribution of reduced and unreduced vowels in unstressed positions, using the 5,294 most frequent word types from the FrePOP Lexicon (Vigário et al, 2015) which represent a corpus of over 2.6 million tokens, shows that 91.5% of all vowels in unstressed position are reduced vowels.…”
mentioning
confidence: 99%
“…Phonological vowel reduction is a general phenomenon in the language affecting all unstressed positions (with few exceptions), so that the contrast between low, mid, and high vowels found in stressed syllables (/i, e, ɛ, a, u, o, ɔ/) does not hold in unstressed syllables. In these syllables, over 90% of all vowels are those that belong to the reduced vowel system, i.e., [i, ɨ, ɐ, u] (data based on the FrePoP Lexicon, Vigário et al, 2015 ). Behavioral findings from adult perception have shown that, in the absence of vowel quality cues, EP speakers are unable to perceive stress contrasts, demonstrating a stress “deafness” effect similar to that found in speakers of languages with fixed stress or no lexical stress ( Correia et al, 2015 ; Lu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%